Impact of Health Education on People with Mental Disorders (ODGJ) on Public Knowledge (Literature Study) - Tinneke A Tololiu; Jusuf Kristianto; Maria Terok; Ellen Pesak; Esther N Tamunu; Herlina Partisse Memah; J Fransiska Pailah (Syntax Corporation Indonesia, 2023)
The World Health Organization (2016) states that the problem of mental health disorders around the world has become a very serious problem. In fact, there are about 35 million people affected by depression, 60 million people affected by person with maniac depression, 21 million people affected by schizophrenia, and 47.5 million affected by dementia. The picture of mental health disorders is also found in Indonesia.